CURRICULUM MANAGEMENT AND ASSESSMENT SYSTEM IN BASIC EDUCATION (DIKDAS) ERA OF INDUSTRIAL REVOLUTION 4.0 - Hisam Ahyani; Rohmat Waluyo; Muntaha Mahfud (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2021)
Introduction/Main Objectives: discusses Curriculum Management and Assessment Systems in the Basic Education Sector (Dikdas) in the Industrial Revolution Era 4.0, including the Implementation of Independent Learning Management in the Era of the Industrial Revolution 4.0, as well as the supporting and inhibiting factors. Background Problems: in order to realize the goals of national education with integrity. Where every citizen has the right to a proper education as stipulated in Law 1945 article 31 paragraph (One) so that in the Industrial Revolution Era 4.0 or the Era of Disruption in which Curriculum Management and Assessment Systems in the Basic Education Sector (Dikdas) need to be carried out properly in supporting and synergize like what the Minister of Education Nadiem Makarim programmed. Novelty: related to the discussion of Curriculum Management and Assessment Systems in the Basic Education Sector (Dikdas) in the Industrial Revolution Era 4.0, including the Implementation of Independent Learning Management in the Era of the Industrial Revolution 4.0, as well as supporting and inhibiting factors so far no one has researched. Research Methods: The research method used is descriptive qualitative research methods, with data sources, books and journals. The data collection technique is done by literature study, data analysis with qualitative data analysis techniques. Finding/Results: Curriculum Management and Assessment System in the Basic Education Sector (Dikdas) Industrial Revolution Era 4.0 related to Freedom of Learning is a new breakthrough, but it is necessary to look at the situation and conditions in certain areas (the impact of the Covid-19 Pancemi) with health protolkol with several precautions such as (wearing masks, and hand washing, and keeping distance). Conclusion : The supporting factors are related to the policy of